Correlations between Epstein‐Barr virus and acute leukemia. Issue 8 (6th March 2017) - Guan, Hongzai; Miao, Hongxia; Ma, Na; Lu, Wei; Luo, Bing
Abstract : Infection with Epstein‐Barr virus (EBV) may be correlated to the onset of acute leukemia (AL). Studies were performed to investigate the relationship between EBV infection and immunophenotyping of acute lymphoblastic leukemia (ALL) and chromosome aberrations. Additionally, the effects of EBV on clinical prognosis were described. Fluorescence quantitative polymerase chain reaction (FQ‐PCR) was used to detect EBV‐DNA copy numbers from bone marrow in 110 cases of patients with ALL, 75 cases of patients with acute myeloid leukemia (AML), and 37 cases of hematologically healthy control subjects. EBV‐DNA copies were found in 64 of 185 (34.6%) patients with AL and 2 of 37 healthy control subjects ( P < 0.001). The EBV infection rate of ALL patients, AML patients, and healthy controls was 40.9% (45/110), 25.3% (19/75), and 5.4% (2/37), respectively. The positive rate of EBV in the ALL and AML groups was higher than in healthy subjects ( P < 0.05). EBV‐DNA copies were found in 1 of 12 (8.3%) T‐ALLs and 44 of 98 (44.9%) B‐ALLs, the positive rate of EBV in B‐ALLs increased significantly compared to the rate of T‐ALLs ( P < 0.05). Chromosome karyotype analysis showed that EBV infection rates in B‐ALL, T‐ALL, and AML patients with chromosome abnormalities were 46.3% (25/54), 33.3% (1/3), and 30% (9/30), respectively. There was no statistical significance between chromosome abnormality and EBV infection ( P > 0.05). In addition, EBV + ‐ALLs had higher relapse and mortality rates than that of EBV − ‐ALLs. Together, we conclude that EBV infection may be correlated with the incidence of AL, and the infection rate of EBV in B‐ALL was higher than that of T‐ALL. EBV‐positive patients showed an unfavorable prognosis.